More and Better Jobs from Crops and Trees in Mozambique - Delgado, Christopher; Costa, Carlos; Ricaldi, Federica (World Bank, Washington, DC, 2021)
This book focuses on entry points for creation of better jobs through agricultural value chains and lays out the policy implications, using cassava, cashew, and plantation forestry as examples. It is based on case studies carried out in 2018-2020 by the World Bank Jobs Group as part of the multi-stakeholder Let’s Work Program in Mozambique. Let’s Work is a global partnership encompassing over 25 private sector organizations, international financial institutions, multilateral development banks, and bilateral donors focused on supporting private sector-led job growth. The study documents opportunities for creating more and better jobs, often in formal employment, linked to the cassava, cashew and plantation forestry value chains. Cassava in Mozambique is currently a traditional subsistence food crop; cashew is a struggling traditional export crop; and plantation forestry is a relatively new sector. However, the study also argues that to realize these opportunities Mozambique requires proactive public policy and investments to overcome significant challenges such as: climate change; over-concentration in current export market destinations; and the unintended side effects of some public policies. The study is focused on promoting an enabling environment for private sector growth in these value chains. It aims to inform ongoing debates about how agriculture and improved natural resource management can contribute more to economic transformation in Mozambique.